Comparative effects of addition of monensin, tannic acid and cinnamon essential oil on in vitro gas production parameters of sesame meal - BESHARATI, M.; PALANGI, V.; MOADDAB, M.; NEMATI, Z.; AYAŞAN, T. (Journal of the Hellenic Veterinary Medical Society, 2021)
The aim of this experiment was to compare the effects of adding monensin, tannic acid and cinnamon essential oil on in vitro gas production parameters of sesame meal. Experimental treatments included sesame meal (control), sesame meal + 12 mg monensin/kg DM, sesame meal + 24 mg monensin/kg DM, sesame meal + 50 mg tannic acid/kg DM, sesame meal + 100 mg tannic acid/kg DM, sesame meal + 150 mg cinnamon essential oil/kg DM, sesame meal + 250 mg cinnamon essential oil/kg DM. The amount of gas produced by treatments fermentation was measured at 4, 6, 8, 12, 16, 24, 36, 48, 72, 96 and 120 hours after incubation. The results showed that gas production decreased significantly in 120 hours after incubation in the treatment containing monensin (at 12 and 24 mg/kg DM) and cinnamon essential oil (at 150 and 250 mg/kg DM) compared to the control treatment (P<0.05). The addition of monensin and cinnamon essential oil had a significant effect on increasing partitioning factor and fermentation efficiency compared to control treatment (P<0.05). Acid tannic at 100 mg/kg DM increased NEL, SCFA, OMDe and microbial protein compared to control (P<0.05). Ammonia nitrogen and total volatile fatty acids concentration at 120 h of incubation showed a significant increase in monensin and tannic acid supplementation compared to control (P<0.05), but cinnamon essential oil significantly decreased ammonia nitrogen concentration. In conclusion, cinnamon essential oil and monensin can be used in an environmentally conducive and acceptable way to diminish biogas emissions from ruminants; therewith ameliorate environmental conditions. However, the cinnamon essential oil can be easily used in livestock diets to improve fermentation and reduce biogas production.